Efforts to Improve Children's Gross Motor Skills (Body Balance) Through the Traditional Game Engklek Class I SD IT Hidayatul Jannah - Masriana, Masriana; Suyono, Suyono; Berutu, Sri Rahmayanti; Suci Ramadani, Karfika (Jurnal Media Informatika, 2024)
This research aims to find out to what extent playing crank can improve the gross motor skills (body balance) of Grade 1 children at SD IT Al Hidayatul Jannah. The type of research used is classroom action research using descriptive analysis methods. Data obtained from observations were analyzed using qualitative descriptions by processing data from observations in the engklek game activity. The subjects in this research were 20 grade 1 students. The results of this research showed that the results of the engklek game activity were almost 100% complete in the game, out of 20 students there were only 3 students who did not complete this balance training game, because they did not understand how to play and did not pay attention to the information provided by the examiner. This shows an increase in learning outcomes for gross motor skills (body balance) carried out in the traditional engklek game.